Upaya Meningkatkan Prestasi Belajar PPKN Siswa Kelas VIIIA SMP Negeri 1 Sekaran dengan Model Pembelajaran TAI (Team Assisted Individualization) Tahun Pelajaran 2019/2020 - Supriyono Supriyono (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2020)
This study aims to improve student achievement by using the Team Assisted Individualization (TAI) learning model. This research is included in action research which is designed into two cycles of activity. Data collection was carried out through observation and tests. From the results of data collection, the results obtained are as the problems raised in this study. From the results of the collaborator teacher's observations on group performance and activities and learning outcomes, step by step changes to a positive direction. With the Team Assisted Individualization (TAI) learning model being applied, students look excited and enthusiastic about learning PPKn. The Team Assisted Individualization (TAI) learning model that was applied turned out to be able to arouse enthusiasm for learning.